Influence of Mn\(^2+\) Doping on Structural Phase Transformation and Optical Property of TiO\(_2\):Mn\(^2+\) Nanoparticles - Loan, Trinh Thi; Long, Nguyen Ngoc (Communications in Physics, 2019)
Titanium dioxide (TiO2) nanoparticles with various Mn2+-doping concentration (from 0 to 12 mol%) were successfully synthesized by the sol–gel method using titanium tetrachloride (TiCl4), and manganese II chloride tetrahydrate (MnCl2.4H2O) as precursors. The phase and crystallinity of the synthesized materials were investigated by powder X-ray diffraction pattern and Raman spectroscopy. Diffuse reflection and photoluminescence spectra were taken to investigate the absorption and emission characteristics of the synthesized samples. The results show that the anatase and rutile phases existed simultaneously in all the doping TiO2 nanoparticles and the Mn2+ doping enhances anatase-rutile transformation. The Mn2+ contents did not affect the lattice of TiO2 host, but affected positions of its Raman modes. The optical band gap of the TiO2:Mn2+ decreases with the increase of doping concentration. Photoluminescence spectra of the TiO2:Mn2+ nanopaticles showed the transitions between the bands, the transitions related to defect states and the Mn2+ ion doping leads to quenching the photoluminescence.